Sociology in theology: reflexivity and belief - Flanagan, Kieran (Palgrave Macmillan, 2007)
This is an original study of the sociological imagination in regard to visual culture. It explores the refelxive dimensions of choice over seeing or not seeing in relation to paintings, images and islands